Recovery of Lost Target Using Target Tracking in Event Driven Clustered Wireless Sensor Network. (14th December 2014) - Patil, Shailaja; Gupta, Ashish; Zaveri, Mukesh
Abstract : The prediction based target tracking in wireless sensor network is being studied from many years. However, the presence of a coverage hole(s) in the network may hamper tracking by causing temporary loss of target, which is a crucial issue in mission critical applications. This raises the need for robust recovery mechanism to capture the lost target. However, the problem of recovery of lost target during tracking has received less attention in the literature. In this paper, we present an energy efficient recovery mechanism. The performance of proposed algorithm for lost target recovery using different tracking filters has been evaluated with and without awakening hole boundary nodes. The efficacy of the algorithm has been tested using various causes of losing target with and without energy saving modes. We have conducted exhaustive simulations for recovery of the lost target and presented the analysis of how the recovery gets affected with linear and nonlinear filters. From the simulation results and energy analysis, it is evident that the proposed recovery algorithm outperforms the existing work in the literature.